Investigating gene expression differences in acute and organotypic mouse hippocampal brain slices as models for studying the brain - Kundieko, Sagel (Department of Human Biology, 2025)
Organotypic brain slice cultures (OBSCs) are widely used to study neural circuit function, but their molecular and cellular composition relative to acute brain slices remains poorly characterized. Here, using single-nucleus RNA sequencing, I performed a comprehensive comparison of gene expression between OBSCs and acute brain slices prepared from postnatal day 7 mouse hippocampus. I identified significant differences in cellular composition, with OBSCs showing an overrepresentation of glial cells and a relative underrepresentation of neuronal populations. Notably, oligodendrocytes were almost exclusively found in OBSCs, while dentate progenitor cells were predominantly present in acute slices, reflecting ongoing developmental processes in culture. Differential gene expression analysis revealed over 4200 unique differentially expressed genes across major cell types, with excitatory neurons and astrocytes showing the most substantial transcriptional changes. Gene ontology analysis demonstrated upregulation of pathways involved in neuronal development and cell signalling alongside downregulation of axon guidance pathways in OBSCs. Specific cell-type analysis revealed distinct adaptations, including altered inflammatory responses in microglia and astrocytes as well as modified synaptic signalling in dentate gyrus cells. These findings provide crucial insights into how brain slice cultures adapt to ex vivo conditions and highlight important considerations for their use as experimental models in neuroscience research.